Diplomacy and Recruitment of Mercenaries before the Battle of Žalgiris - Ekdahl, Sven (Lietuvos istorijos studijos, 2010)
During the months preceding the battle of Žalgiris (Tannenberg/Grunwald) the diplomatic activity of the countries involved was intense. After the successful campaign of the Teutonic Order against Poland in 1409 an armistice was concluded on 8 October between Grand Master Ulrich von Jungingen and King Jagiello (Jogaila) of Poland and the war was postponed until the end of St John’s Day in 1410. The truce did not include Grand Duke Vytautas and the Grand Duchy of Lithuania. An arbitration had to be announced by King Venceslas of Bohemia on 9 February 1410 at the latest. In the meantime, in December 1409, Jagiello and Vytautas met at Brest-Litowsk in order to discuss and prepare a campaign against Prussia after the end of the armistice. Ulrich von Jungingen for his part concluded a treaty against Poland with King Sigismund (or Sigmund) of Hungary, vicarius generalis of the Holy Roman Empire. According to a Prussian chronicler the arbitration of King Venceslas was pronounced in Prague on 8 February 1410. It was clearly in favour of the Teutonic Knights and was therefore not accepted by the Polish delegates who left the Bohemian capital in anger. Sigismund now decided to replace his brother Venceslas as a mediator and arranged a meeting with Vytautas in the Hungarian city of Klismark (the German name; in Hungarian Kesmark, in Polish Kiezmark, today Kežmarok in Slovakia). He obviously tried to break up the Polish-Lithuanian union by offering the Lithuanian Grand Duke a king’s crown, but without success. He also got in contact with Jagiello, who dwelled nearby in the town of Nowy Sącz on the Polish side of the border. The most important result of the negotiations in Klismark was the decision to meet again in the Prussian city of Thom (Polish: Torwi) in June, before the end of the truce between Prussia and Poland. It was expected to be a most important meeting between the Grand Master of the Teutonic Order, the Lithuanian Grand Duke and the Kings of Poland and Hungary. Ulrich von Jungingen got this message by the king’s emissary on 11 May and immediately stopped the preparations for an intended surprise attack on Poland on 1 June. He had regarded such an attack as legitimate, because the Poles had rejected the arbitration by King Venceslas, and had for that purpose secretly recruited 1,800 mercenaries. Now his war machinery had been brought to a standstill by his mighty ally. However, neither the kings of Hungary and Poland, nor the grand duke of Lithuania appeared in Thom, where Ulrich von Jungingen expected them to come in mid-June. The most fateful consequence of the decision in Klismark and the broken-off preparations for a surprise attack on Poland on 1 June 1410 influenced the recruitment of mercenaries by the Order. The Grand Master had started a recruiting campaign, but stopped it immediately after receiving the message from Sigismund on 11 May. Two weeks later, however, he ordered the Order’s emissary, who dwelled in Prague, to recruit 900 mercenaries so that they would be in Prussia before the end of the truce on St John’s Day. These two weeks with contradictory orders caused a catastrophe for the Teutonic Knights. Many mercenaries, who originally had expected to be enrolled in the Order’s army, were so disappointed and angry because of being refused that they instead offered their war service to the king of Poland. The total number of those soldiers who then changed sides is not known, but a letter to the Grand Master tells at least about two big troops of Bohemian mercenaries. There might have been more. Another consequence of the postponed recruiting campaign, which was resumed partly on 24 May and fully at the beginning of June, can be deducted from the information in the Payment book of the Teutonic Order (Soldbuch). That important source shows evidence that about 2,000 mercenaries arrived too late to join the main army when it marched from Thorn at the beginning of July in order to stop the expected intervention. It is obvious that Ulrich von Jungingen had reactivated his recruiting campaign too late. He had relied in vain upon the promises of Sigismund and then had to face the fatal consequences of that policy. We may thus conclude that the mighty Teutonic Order in Prussia had been thrown down from the peak of power within a few weeks, because its military planning, preparations and possibilities were undermined in the diplomatic battle for power. Some thousand mercenaries had arrived too late or had offered their war service to the king of Poland instead of to the Grand Master of the Order. This is surely one of the most important facts when looking for the causes of the disastrous defeat of the Knights on 15 July 1410, even when considering other facts like the disadvantageous location of the battlefield, the unfavourable position of the sun (dazzling the troops of the Order) or the feigned retreat of a part of the Lithuanian army. No wonder that the Order even years later bitterly complained about the role of King Sigismund during the months preceding the battle.